Development of the Nervous System of Carinina ochracea (Palaeonemer-tea, Nemertea) - von Döhren, Jörn (PLOS ONE, 2016)
The various clades of Lophotrochozoa possess highly disparate adult morphologies. Most of them, including Nemertea (ribbon worms), are postulated to develop via a pelagic larva of the trochophora type, which is regarded as plesiomorphic in Lophotrochozoa. With respect to the nervous system, the trochophora larva displays a set of stereotypic features, including an apical organ and trochal neurites, both of which are lost at the onset of metamorphosis. In the investigated larvae of Nemertea, the nervous system is somewhat divergent from the postulated hypothetical trochophore-like pattern. Moreover, no detailed data is available for the “hidden” trochophore larva, the hypothetical ancestral larval type of palaeonemertean species. Therefore, the development of the nervous system in the larva of Carinina ochracea, a basally branching palaeonemertean species, was studied by means of immunofluorescence and confocal laserscanning microscopy. Like in the other investigated nemertean larvae, the prospective adult central nervous system in C. ochracea develops in an anterior to posterior direction, as an anterior brain with paired longitudinal nerve cords. Thus, development of the adult nervous system in Nemertea is largely congruent with currently accepted hypotheses of nervous system development in Spiralia. In early development, transitory apical, serotonin-like immunoreactive flask-shaped cells are initially present, but the trochal neurites that have been considered as pivotal to lophotrochozoan development, are absent. In the light of the above stated hypothesis, trochal neurites have to be interpreted as reduced in Nemertea. On the other hand, due to the unsettled systematic status of Palaeonemertea, more comparative data are desirable to answer the remaining questions regarding the evolution of nervous system development in Nemertea.